A house purchase transaction that has been paid in full but the sale and purchase deed has not been executed by PPAT, resulting in losses for the buyer (Case Study Number: 15/Pdt.G/2023/PN.Gdt) - Zaini, Zulfi Diane; Indroko, Farel Ade Ari (International Journal of Religion Education and Law, 2024)
This research examines the juridical aspects of the collateral object of the credit agreement that was entered into by the developer and has been sold in full to the buyer. The research background involves the complexity of property transactions, where house ownership certificates are often used as collateral for credit loans. However, cases of non-compliance and fraud by developers and Notaries/PPATs can be detrimental to buyers, especially in cases that occurred at Feros Estate Housing, Pesawaran Regency, Lampung Province. The problem of this research is: What is the legal protection for home buyers whose objects have been guaranteed in advance by the developer to the bank (Case Study Number: 15/Pdt.G/2023/PN.Gdt)? and Legal consequences that arise between the home buyer and the bank as a result of the object having become a collateral object in the banking credit agreement (Case Study Number: 15/Pdt.G/2023/PN.Gdt)? The research method used in this research is a normative and empirical juridical approach using secondary and primary data. Next, the analysis is carried out qualitatively. As a discussion in this research, there is legal protection for home buyers whose objects have been guaranteed in advance by the developer to the bank based on Case Number: 15/Pdt.G/2023/PN.Gdt, namely: The existence of a Land Deed Making Officer (PPAT) Professionals are the main guarantors in ensuring accuracy, legal security and high professionalism in every transaction. PPAT has a big role, starting from checking the legality of documents to making a Sale and Purchase Deed (AJB), which provides legal certainty to buyers. Legal protection for home buyers does not only depend on the seller, but also on PPAT's obligation to provide complete information, check the legality of documents, and ensure the transaction process complies with established standards and regulations. Next is a discussion of the research regarding the legal consequences that arise between the home buyer and the bank as a result of the object having become a collateral object in a banking credit agreement based on Case Number: 15/Pdt.G/2023/PN.Gdt, namely: In a house buying and selling transaction with objects pledged as collateral to the bank, it can be concluded that the situation involves a complex series of risks and legal consequences. Several parties such as buyers, sellers, PPAT, and banks may face legal action depending on their role and contribution in the transaction. In house buying and selling transactions with objects pledged as collateral to the bank, high vigilance and the involvement of professional parties are required to mitigate legal risks that may arise. Preventive measures and awareness of legal aspects are very important to ensure the smoothness and validity of property transactions. The suggestions in this research are: The legal protection provided to home buyers in home buying and selling transactions is considered to be inadequate in protecting and providing rights for the community, especially prospective home buyers, the process is still quite complicated and many people didn't know it. So the relevant authorities, such as BPN, can increase supervision and carry out internal audits of PPAT. This is done in order to help and ensure that PPAT carries out its duties properly and provides maximum legal protection. Furthermore, the Government can do several things to reduce legal consequences, one of which is strengthening consumer protection regulations related to property transactions, especially when involving banks or PPAT.